2010
DOI: 10.4163/kjn.2010.43.6.628
|View full text |Cite
|
Sign up to set email alerts
|

Intakes and Major Food Sources of Vitamins A and E of Korean Adults Living in Seoul and Gyeonggi Province

Abstract: To determine vitamin A and E intakes and their food sources, dietary intakes were collected by three consecutive 24-hour recalls from 192 adults living in Seoul and Gyeonggi Province, Korea. The mean vitamin A, retinol and β-carotene intakes were 1240.1 ± 1101.1 μg retinol equivalent/day (693.3 ± 563.2 μg retinol activity equivalent/day), 182.6 ± 149.5 μg/ day and 5443.3 ± 6365.5 μg/day, respectively. Only 9.4% of the subjects consumed less than the Korean Estimated Average Requirement for vitamin A. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…30 GT metabolite, 2,7,8-trimethyl-2-(b-carboxuethyl)-6-hydroxychroman (g-CEHC), significantly inhibited cyclooxygenase-2 activity in lipopolysaccharide-activated macrophages and IL-1b-treated epithelial cells although g-CEHC was easily excreted. [30][31][32] Previous studies suggested that GT has a potential role in regulation of oxidative stress and inflammation at low dose (33 mg/kg body weight) in murine models. 30,31 Because of its strong nucleophilic properties, GT may be a more potent pro-apoptotic agent than AT in trapping ROS in colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…30 GT metabolite, 2,7,8-trimethyl-2-(b-carboxuethyl)-6-hydroxychroman (g-CEHC), significantly inhibited cyclooxygenase-2 activity in lipopolysaccharide-activated macrophages and IL-1b-treated epithelial cells although g-CEHC was easily excreted. [30][31][32] Previous studies suggested that GT has a potential role in regulation of oxidative stress and inflammation at low dose (33 mg/kg body weight) in murine models. 30,31 Because of its strong nucleophilic properties, GT may be a more potent pro-apoptotic agent than AT in trapping ROS in colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the analysis, we considered three main groups and 14 subgroups of this category of food. We compared our results with the other studies published in the scientific literature on the Australian [ 66 ], Spanish [ 67 , 68 ], American [ 69 , 70 ], Korean [ 71 , 72 ], UK [ 61 ], and Dutch [ 73 ] populations. Such a comparison was made for energy and those nutrients whose supply in the Polish diet is 20% and more.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have shown that high intakes of carotenoids are associated with relatively low risks of chronic diseases including cardiovascular disease and certain types of cancers [ 6 - 8 ]. Korean adults obtain their vitamin A mainly from plant foods [ 10 ]. Therefore, higher intakes of carotenoids of Korean adults may play an essential role in potent antioxidant concentrations and modulating the pathogenesis of several chronic degenerative diseases [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Noh et al [10] reported that Korean adults obtained over 80% of vitamin A from plant foods. Although average vitamin A intakes of Koreans are over the Recommended Nutrient Intakes (RNI) given as µg RE [9], the vitamin A status of Koreans may not be acceptable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation